Facilitating Trade through Rules of Origin: A Consideration of the African Continental Free Trade Area - Okoroma, Blessing Ijeoma (University of Calgary, 2024)
Rules of origin play a pivotal role in free trade agreements. Apart from serving as a tool to distinguish goods by determining the nationality of a product, rules of origin have the capacity to increase trade relations or deter it. Of course, it is the hope of any viable state to increase profitable trading relations, and if rules of origin can help with that, it becomes expedient to fully understand how these rules of origin operate. In Africa, we see rules of origin being implemented amongst the Regional Economic Communities (RECs), but this has come with many struggles. In fact, low intra-African trade can be narrowed down to complex rules of origin regimes deployed in regional agreements in Africa. As of date, the major RECs have each implemented different rules of origin, leading to the co-existence of conflicting rules of origin across Africa. This non-uniformity in the rules of origin regimes in Africa has resulted in low continental trade in Africa. As such, these RECs have not yielded the expected increase in intra-African trade. With the creation of the African Continental Free Trade Area (AfCFTA), which currently doubles as the latest and largest FTA in Africa, it is expected that better rules of origin will be deployed to mitigate the existing intra-African trade deficits. This thesis thus deploys a doctrinal approach in determining whether AfCFTA’s rules of origin are positioned to achieve greater intra-African trade. Consequently, this thesis uncovers some lapses in AfCFTA’s rules of origin and calls for harmonization of all the rules of origin in Africa and recommends a possible amendment to Article 19 of the Agreement establishing AfCFTA to accommodate the intended harmonization.
Keywords: African Continental Free Trade Area; Free Trade Area; Rules of Origin